Shadow Banking and Financial Stability under Limited Deposit Insurance - Lukas Voellmy (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper proposes a new theory of shadow banking that highlights the role of the cap on deposit insurance at traditional banks. Very risk averse investors with large endowments (institutional cash-pools) are looking for the best alternative to insured bank deposits. This is provided by shadow banks that invest exclusively in assets with very low credit risk. In equilibrium, investors face a trade-off between shadow banks with low fundamental risk and commercial banks with low run risk.
Keywords: G2; 330